Sinkronisasi Kurikulum Mata Kuliah Wajib Umum Pancasila, Kewarganegaraan, dan Agama di Perguruan Tinggi Dalam Melawan Radikalisme - Zulkarnain, ZULKARNAIN; Basri, Basri; Matang, Matang; Wiranata, Irawan Hadi (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2021)
This paper wants to explain the efforts that lecturers should make in universities tofight and prevent the development of radicalism in universities by synchronizing thecurriculum in general compulsory subjects such as Pancasila, Citizenship, andReligious education. This research uses a descriptive qualitative method with a casestudy approach. This research was conducted at the internal quality assurance centerof the Politeknik Negeri Balikpapan in curriculum development for general coursesin fighting radicalism and the civic education lecturer team outside the PoliteknikNegeri Balikpapan. The results of the study would like to recommend curriculumsynchronization, among others: first, synchronizing the design of semester learningmaterials about radicalism in Pancasila, Citizenship, and Religious Education,secondly implementing a hidden curriculum in countering the development ofradicalist ideology, third conducting joint evaluations and research on thedevelopment of radicalism in higher education. Sustainable.